Revisiting the Effect of Family Involvement on Corporate Social Responsibility: A Behavioral Agency Perspective - Cui, Victor; Ding, Shujun; Liu, Mingzhi; Wu, Zhenyu (2018)
This paper sheds light on the incongruent findings concerning the relationship between family involvement and firms’ corporate social responsibility (CSR). While prior studies have mainly taken the perspective of families’ socioemotional wealth preservation, we approach this relationship from the perspective of behavioral agency theory, highlighting the important role played by CEOs’ family memberships. Specifically, we posit that family firms are more likely to invest in CSR when their CEOs are members of the controlling families. Furthermore, we examine how family firms can employ long-term incentives to encourage non-family CEOs to act in the interests of the controlling families to preserve SEW and thus enhancing family firms’ CSR performance. We tested our hypotheses using hand-collected data of family firms included in the S&P 500 index, in the period of 2003–2010. The empirical findings support our hypotheses that (a) family firms with family members as the CEOs have better CSR performance and (b) family firms tend to provide a high level of long-term incentives to non-family than family CEOs. In addition, long-term incentives strongly motivate CEOs to improve firms’ CSR performance, regardless of their family memberships.
Keywords: Socioemotional wealth; Long-term incentives; CEOs’ family membership; Behavioral agency theory; family involvement; Corporate Social Responsibility